(untitled) (Journal of the College of Basic Education, 2023)
The importance of fuel filling stations has increased in Iraq at the present time with the expansion of city areas and the increase in the number of cars, "which resulted in an uneven distribution of stations on different city sites, and that the main task of fuel stations is to meet the needs of the population and vehicles with fuel derivatives," and fuel filling stations represent An important vital part of land uses for transportation and services purposes, as it is the main source for supplying vehicles of various types and providing residents in residential areas with oil derivatives, so it is an important element as it is available in most parts of cities and distributed on all types of transportation methods, as the increase in the consumption of multiple energy sources, including Transport fuel of both types (gasoline, gas oil) has led to interest in establishing fuel filling stations in a way that is appropriate to the size of the population and to serve the means of transport of all kinds in the country.